MAC schemes collision reduction for LDACS2 (Al-Mansour Journal, 2022)
To meet the future capacity requirements in aeronautical communication, new aeronautical systems are proposed, namely LDACS1 and LDACS2, respectively. Since L-band Digital Aeronautical Communication System 2 (LDACS2) is a TDMA system, the possibility for MAC layer collision in the login phase is higher than that of LDACS1, which is FDMA. In this paper, the specified MAC login algorithm in LDACS2 is simulated. The results show high collision rate. On the other hand, extending the LoG2 section shows less collision rate using the same login algorithm.
Keywords: Aeronautical Communication; LDACS2; TDMA; MAC